Upregulation of FGD6 Predicts Poor Prognosis in Gastric Cancer - Zeng, Jianmin; Li, Man; Shi, Huasheng; Guo, Jianhui (Frontiers in Medicine, 2021)
Background: The aim of this study investigated the prognostic significance of faciogenital dysplasia 6 (FGD6) in gastric cancer(GC). Methods: The data of gastric cancer patients from TCGA database were used for the primary study. Kaplan–Meier method was explored the relationship between FGD6 and overall survival time. Logistic regression and Univariate Cox regression were analyzed the relationships between the FGD6 level and various clinicopathological features. Multivariate Cox regression analysis was used to evaluate whether FGD6 was an independent prognostic factor for survival of patients with GC. In addition, Gene set enrichment analysis (GSEA) was performed to investigate the possible biological processes of FGD6. Results: FGD6 level was significantly overexpressed in GC tissues, compared with adjacent normal tissues. The high expression of FGD6 was related to high histological grade, stage, T classification and poor prognosis of gastric cancer. Multivariate cox regression analyses showed that FGD6 was an independent prognostic factor for survival of patients with gastric cancer. Gene Set Enrichment Analysis (GSEA) identified that high expression of FGD6 was mainly enriched in Regulation of actin cytoskeleton. Conclusion: FGD6 may be a prognostic biomarker for predicting the outcome of patients with GC.